2020
DOI: 10.1111/joim.13060
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aortic aneurysms: pathophysiology and clinical issues

Abstract: Click here to view the Original article by Dr. Langenskiöld et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 10 publications
(37 reference statements)
0
12
0
1
Order By: Relevance
“…Keywords: abdominal aortic aneurysm, animal model, retroperitoneal approach, elastase, calcium chloride, beta aminopropionitrile BACKGROUND Abdominal aortic aneurysm (AAA) is one of the most challenging cardiovascular diseases and usually has no symptoms but has the risk of spontaneous dilation and rupture. Once the aneurysm ruptures, the mortality rate is as high as 80% (1). Because of its potential lethality, AAA has always been a research hotspot.…”
Section: Resultsmentioning
confidence: 99%
“…Keywords: abdominal aortic aneurysm, animal model, retroperitoneal approach, elastase, calcium chloride, beta aminopropionitrile BACKGROUND Abdominal aortic aneurysm (AAA) is one of the most challenging cardiovascular diseases and usually has no symptoms but has the risk of spontaneous dilation and rupture. Once the aneurysm ruptures, the mortality rate is as high as 80% (1). Because of its potential lethality, AAA has always been a research hotspot.…”
Section: Resultsmentioning
confidence: 99%
“…At present, it is suggested that inflammation initiates the pathological process of AAA, followed by degradation of the ECM ( Lattanzi, 2020 ). However, some studies have indicated that media ECM degradation caused by various physical and chemical factors aggravates inflammation and immune cell infiltration ( Cai et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The development of AAA is related to a focal dilatation of the abdominal aorta measuring 50% greater than the normal proximal segment or >3 cm in maximum diameter. The progression of AAA can lead to aneurysm rupture, an event that reaches 60–80% of mortality [ 11 , 12 , 13 , 14 , 15 ]. In turn, CVD is defined as a syndrome of chronic morphological and functional abnormalities in the venous circulation of the lower extremities, resulting from venous valve incompetence, venous reflux, and venous hypertension [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In turn, CVD is defined as a syndrome of chronic morphological and functional abnormalities in the venous circulation of the lower extremities, resulting from venous valve incompetence, venous reflux, and venous hypertension [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ]. Despite the different clinical images of these diseases, they share many common pathological conditions, including endothelial dysfunction, inflammatory response, and vascular remodeling [ 6 , 7 , 11 , 12 , 16 , 17 , 20 ]. Furthermore, the high prevalence, multifactorial character, and burden of severe life-threatening consequences of these diseases made them major global health problems [ 6 , 8 , 9 , 10 , 13 , 14 , 15 , 18 , 19 , 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%